2017
DOI: 10.1002/casp.2338
|View full text |Cite
|
Sign up to set email alerts
|

School climate and ethnic‐racial identity in school: A longitudinal examination of reciprocal associations

Abstract: The messages youth receive in schools about how they matter as individuals and as members of ethnic-racial groups are influential in constructing their developing ethnic-racial identities (ERI).However, the developing ERI students hold also have a role in shaping their experiences at school. The current study examined the longitudinal and reciprocal association between ERI (exploration and resolution) and school climate (support for cultural pluralism and teacher supportiveness) among 491 Black, Latino, and Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Thus, adolescents who participated in the Identity Project and who had a clearer understanding of their heritage identity not only had more positive perceptions of the self at post‐intervention, but also more positive views of those with different cultural backgrounds. Fostering a better understanding of who adolescents are in terms of their cultural heritage, worldviews, and values can help them understand themselves in relation to other groups and also promote empathy for diverse others (Camacho et al., 2018; Mathews et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, adolescents who participated in the Identity Project and who had a clearer understanding of their heritage identity not only had more positive perceptions of the self at post‐intervention, but also more positive views of those with different cultural backgrounds. Fostering a better understanding of who adolescents are in terms of their cultural heritage, worldviews, and values can help them understand themselves in relation to other groups and also promote empathy for diverse others (Camacho et al., 2018; Mathews et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, adolescents who perceived their schools as endorsing cultural pluralism and providing opportunities to learn about diverse heritage cultures engaged in greater cultural heritage identity exploration and commitment (Moscardino et al., 2019; Schachner et al., 2016). A longitudinal study in the United States found that middle school adolescents who perceived more support for cultural pluralism showed greater ethnic–racial identity exploration and resolution (Camacho et al., 2018). Further, greater ethnic–racial identity exploration and resolution led to more positive perceptions of the cultural diversity climate, at least for white adolescents.…”
Section: Classroom Cultural Diversity Climate and Ethnic–racial Identmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study focused on an analytic sample of 367 (70% African American and 30% Latinx; 51% girls) students (37% sixth graders, 43% seventh graders, and 20% eighth graders) from one middle school (see Camacho, et al, 2018 for information about the full sample). The original sample comprised 386 self-identified African American and Latinx students; however, 19 students did not have gender or grade-level data, which were considered as possible covariates to be included in the analysis and thus these students were omitted from the current sample.…”
Section: Methodsmentioning
confidence: 99%
“…These interactions between teachers and students and among students can reveal anxieties—or conversely, ease and comfort—with ethnic/racial diversity and difference (Stevenson, 2014). Furthermore, previous empirical research demonstrated that the quality of student–teacher relationships and support for multiculturalism and diversity in school were positively associated with greater ethnic-racial identity exploration 6 months later (e.g., Camacho et al, 2018). For the purpose of the present study, the implementation of the Developmental Designs approach implies support for a classroom and school community conducive to youth’s exploration of diverse life experiences and backgrounds, and we reason that this could include those pertinent to ethnic-racial identity.…”
Section: Schooling School-based Social-emotional Learning and Ethnimentioning
confidence: 95%